O fluxo da vida no espaço fragmentado: conflitos ambientais e gestão da água em Viçosa - MG - Silvano Souza Dias (2014)
The main objective of this work is to analyze water management in Viçosa, Minas Gerais, from the dynamics of environmental conflicts that occur in that county. We understand that water should be approached from a spatial perspective, as the current crisis over this so-called natural resource, as well as conflicts and environmental injustices often originate from the hegemonic way society produces its space, which nowadays is the capitalist production of space. We intend to verify in this context in which water issues become a problem for a significant portion of society and what environmental conflicts can reveal about their management. We aim to highlight the actors involved in the conflict, as well as the discourses that seek to legitimize the different perspectives in dispute. Also, we identify which answers are offered institutionally to the problems and conflicts within the water management and its interconnection with other forms of spatial management at local level. As a qualitative study, the methodology used was based on analysis of the local news media to identify the main conflicts in the region, interviews with leaders and residents in the neighborhoods and communities and with government representatives to verify the underlying causes and the conflicts and institutional responses. Finally, the information was complemented by the observation of public meetings and analysis of documents, laws and technical reports.